Occurrence and diversity of stem nodulation in Aeschynomene and Sesbania legumes from wetlands of Madagascar - Faustin F. Manantsoa; Marrino F. Rakotoarisoa; Clémence Chaintreuil; Adamson T. E. Razakatiana; Frédéric Gressent; Marjorie Pervent; Mickaël Bourge; Martial D. Andrianandrasana; Nico Nouwen; Herizo Randriambanona; Heriniaina Ramanankierana; Jean-François Arrighi (Scientific Reports, 2024)
Abstract Legumes have the ability to establish a nitrogen-fixing symbiosis with soil rhizobia that they house in specific organs, the nodules. In most rhizobium-legume interactions, nodulation occurs on the root. However, certain tropical legumes growing in wetlands possess a unique trait: the capacity to form rhizobia-harbouring nodules on the stem. Despite the originality of the stem nodulation process, its occurrence and diversity in waterlogging-tolerant legumes remains underexplored, impeding a comprehensive analysis of its genetics and biology. Here, we aimed at filling this gap by surveying stem nodulation in legume species-rich wetlands of Madagascar. Stem nodulation was readily observed in eight hydrophytic species of the legume genera, Aeschynomene and Sesbania, for which significant variations in stem nodule density and morphology was documented. Among these species, A. evenia, which is used as genetic model to study the rhizobial symbiosis, was found to be frequently stem-nodulated. Two other Aeschynomene species, A. cristata and A. uniflora, were evidenced to display a profuse stem-nodulation as occurs in S. rostrata. These findings extend our knowledge on legumes species that are endowed with stem nodulation and further indicate that A. evenia, A. cristata, A. uniflora and S. rostrata are of special interest for the study of stem nodulation. As such, these legume species represent opportunities to investigate different modalities of the nitrogen-fixing symbiosis and this knowledge could provide cues for the engineering of nitrogen-fixation in non-legume crops.